STUDI PENATAAN SARANA PRASARANA TEMPAT PELELANGAN IKAN (TPI) JUANDA BERBASIS CLUSTER - Dhini Nadia; Suning Suning (Fakultas Teknik , Universitas PGRI Adi Buana Surabaya, 2014)
Coastal and marine areas is one of the natural resources that have the nature of a complex, dynamic, and unique because of the influence of the two ecosystems, the oceans andterrestrial ecosystems. Sidoarjo has great potential in the development of the fisheries sector, onein the District Sedati, Gisik Cemandi village. Cemandi Gisik village has the potential local-scalefish auction place. The purpose of the study is to identify the Fish Auction Infrastructures Juanda,and create a concept of structuring infrastructure cluster-based TPI. The method used isdescriptive qualitative method and arrangement of the design concept. Analytical techniques usedwere interviews and observation techniques in the study area. The analysis showed that thearrangement of the TPI-based cluster, can be carried out if the following Regulation of MaritimeFisheries and Affairs 10 / MEN / 2004, relating to facilities and infrastructure. Existing facilities andinfrastructure in the corresponding Regulation of the Minister of Marine Fisheries and Affairs ofIndonesia No. 10 / MEN / 2004 include boat docks, fishing boats, places of worship and toilet,while the infrastructure is not in accordance with the regulation of the Minister of Marine Affairsand Fisheries 10 / MEN / 2004 include building TPI, TPI management office, and fishing gear.Thus, TPI infrastructure that is in conformity with the Regulation of the Minister of Marine Fisheriesand Affairs of Indonesia No. 10 / MEN / 2004 keep being maintained and adjusted in accordancewith the design concept of the arrangement of this research.